2016
DOI: 10.1128/mcb.01096-15
|View full text |Cite
|
Sign up to set email alerts
|

RNA Activation of the Vascular Endothelial Growth Factor Gene (VEGF) Promoter by Double-Stranded RNA and Hypoxia: Role of Noncoding VEGF Promoter Transcripts

Abstract: f RNA activation (RNAa) is a gene regulation process in which promoter-targeted short double-stranded RNAs (dsRNAs) or microRNAs (miRs) induce target gene expression at the transcriptional level. Here, we investigate the presence of cryptic promoter transcripts within the VEGF promoter. Single-strand sense and antisense noncoding vascular endothelial growth factor (NcVEGF) promoter transcripts are identified, and their respective expression is studied in cells transfected with a VEGF promoter targeted dsRNA, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 31 publications
2
17
0
Order By: Relevance
“…Although the dynamics of polymerase pausing are well understood in cell culture [19][20][21], to date there have been few studies that have comprehensively characterized pausing in vivo [22].At potential sites of transcription initiation outside of annotated TSSs, in most cases surveillance and degradation by the nuclear exosome occurs rapidly [23,24]. This degradation is likely important because initiation at non-canonical or cryptic promoters can interfere with coding transcripts or create a deleterious load of non-functional ones, including dsRNAs [25]. In general, sites of initiation unassociated with annotated gene promoters have a high propensity for nucleosome occupancy, and are energetically unfavorable for assembly of the PIC [4,5].…”
mentioning
confidence: 99%
“…Although the dynamics of polymerase pausing are well understood in cell culture [19][20][21], to date there have been few studies that have comprehensively characterized pausing in vivo [22].At potential sites of transcription initiation outside of annotated TSSs, in most cases surveillance and degradation by the nuclear exosome occurs rapidly [23,24]. This degradation is likely important because initiation at non-canonical or cryptic promoters can interfere with coding transcripts or create a deleterious load of non-functional ones, including dsRNAs [25]. In general, sites of initiation unassociated with annotated gene promoters have a high propensity for nucleosome occupancy, and are energetically unfavorable for assembly of the PIC [4,5].…”
mentioning
confidence: 99%
“…Since the recent identification of RNA activation, several studies have found that miRNAs positively regulate gene expression by targeting promoter elements (32)(33)(34)55). Our previous work revealed that viral and cellular miRNAs target sequences near the TATA-box with high activation efficiency (35).…”
Section: Discussionmentioning
confidence: 99%
“…In 2006, Li et al (29) revealed that small dsRNAs induced gene expression by targeting sequence-specific sites located no more than 1 kb upstream of the transcriptional start site. Small RNA-guided transcription induction (known as RNA activation) has been reported for different target genes in mammals and Caenorhabditis elegans, indicating that this phenomenon is a general mechanism for gene regulation (30)(31)(32)(33)(34). By dissecting the mechanism of an HIV type 1-derived miRNA, our group unexpectedly revealed a novel and broad regulatory mechanism by which miRNAs enhance the activities of several viral and cellular promoters through sequence-specific interactions with the TATA-box motif (35)(36)(37)(38).…”
mentioning
confidence: 89%
“…Expression assays were generated in triplicate for three mRNAs (18S rRNA [16], ACTB [17], and GAPDH) [18]). The FastStart Essential DNA Green Master Kit (Roche LifeScience) was used for amplification (Additional file 1).…”
Section: Mrna Qpcrmentioning
confidence: 99%